Factors That Determine Behavioral Intentions in Using E-Commerce with the Most Visitors in Indonesia - Lestari, Diva Agnes Ayu; Fajar, Ahmad Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to find out what factors influence behavioral intentions in using an e-commerce with the most visitors in Indonesia. The model used in this study is a combination of variables from several previous models related to the problem and variables relevant to this study such as Perceived Ease of Use, Perceived Usefulness, Effort Expectancy, Social Influence, Subjective Norm, and Behavioral Intention. Data collection in this study was to distribute questionnaires online. The questionnaire distributed produced 100 respondents and was processed with SPSS. From the results of processing with the T Test and Double Linear Regression, there are two hypotheses accepted and three hypotheses rejected, which states that the perceived ease of use and effort expectancy variables have a positive significant influence on behavioral intention, while perceived usefulness, social influence and subjective norm do not have a significant influence on behavioral intention.